Anthocyanin and Flavonol Glycoside Metabolic Pathways Underpin Floral Color Mimicry and Contrast in a Sexually Deceptive Orchid - Wong, Darren C. J.; Perkins, James; Peakall, Rod (Frontiers in Plant Science, 2022)
Sexually deceptive plants secure pollination by luring specific male insects as pollinators using a combination of olfactory, visual, and morphological mimicry. Flower colour is a key component to this attraction, but its chemical and genetic basis remains poorly understood. Chiloglottis trapeziformis is a sexually deceptive orchid which has predominantly dull green-red flowers except for the central black callus projecting from the labellum lamina. The callus mimics the female of the pollinator and the stark colour contrast between the black callus and dull green or red lamina is thought to enhance the visibility of the mimic. The goal of this study was to investigate the chemical composition and genetic regulation of temporal and spatial colour patterns leading to visual mimicry, by integrating targeted metabolite profiling and transcriptomic analysis. Even at the very young bud stage, high levels of anthocyanins were detected in the dark callus, with peak accumulation by the mature bud stage. In contrast, anthocyanin levels in the lamina peaked as the buds opened and became reddish-green. Coordinated upregulation of multiple genes, including dihydroflavonol reductase and leucoanthocyanidin dioxygenase, and the downregulation of flavonol synthase genes (FLS) in the callus at the very young bud stage underpins the initial high anthocyanin levels. Conversely, within the lamina, upregulated FLS genes promote flavonol glycoside over anthocyanin production, with the downstream upregulation of flavonoid O-methyltransferase genes further contributing to the accumulation of methylated flavonol glycosides, whose levels peaked in the mature bud stage. Finally, the peak anthocyanin content of the reddish-green lamina of the open flower is underpinned by small increases in gene expression levels and/or differential upregulation in the lamina in select anthocyanin genes while FLS patterns showed little change. Differential expression of candidate genes involved in specific transport, vacuolar acidification, and photosynthetic pathways may also assist in maintaining the distinct callus and contrasting lamina colour from the earliest bud stage through to the mature flower. Our findings highlight that flower colour in this sexually deceptive orchid is achieved by complex tissue-specific coordinated regulation of genes and biochemical pathways across multiple developmental stages.